287 Real-life efficacy of a multi-ingredient coriolus versicolor-based vaginal gel in high-risk hpv patients: interim analysis. (4th December 2020) - Gaslain, Yann; Cortés, Javier; Santiago, Javier de; Sanjuán, María Pilar; Agenjo, Marta; Fiol, Gabriel; Garcia, Carmen; Gurrea, Marta; Hernández, Perla
Abstract : Introduction/Background: Real-life studies inform on the 'effectiveness' of a treatment what is intended to do in routine circumstances. The aim of this study is to evaluate the efficacy of Papilocare® - a multi-ingredient Coriolus versicolor-based vaginal gel- on repairing high-risk (HR) HPV-dependent low-degree cervical lesions and HR-HPV clearance in real-life practice. Methodology: Observational, multicenter, prospective, one-cohort study (PAPILOBS study ClinicalTrial.gov: NCT04199260 ). Currently recruiting 300 vaccinated or not HPV-positive women aged > 25y with Pap smear of ASCUS or LSIL and concordant colposcopy during routine clinical visits in Spain. Patients are treated with Papilocare® 1 cannula/day for 21 days the first month + 1 cannula/alternate days for 5 months. After this 6-month period, patients with altered cytology and/or HPV persistency are treated for a 6-month extension treatment period with the same dosage. Interim analysis of HR-HPV patients with normal Pap smear and concordant colposcopy image (primary endpoint) and patient with HR-HPV cleared (patients with total clearance or partial clearance together with negative Pap smear and normal colposcopy) at 6/12 months is presented. The study was approved by the ethical committee of Public University Hospital of Puerta de Hierro (Madrid). Informed consent was signed by all patients. Results: At 6 months, data of 148 and 146 patients for Pap smear/colposcopy and HR-HPV presence, respectively, were available. 67.6% of patients (100/148) had negative Pap smear and concordant colposcopy. HR-HPV clearance was observed in 58.9% of patients (86/146). Data of 46 and 44 patients included in the 6-month extension treatment period for Pap smear/colposcopy and HR-HPV presence, respectively, were available. At 12 months, 78.3% (36/46) of patients had negative Pap smear and concordant colposcopy and HR-HPV clearance was observed in 70.5% (31/44). Considering all study period, 77% (114/148) and 72.6% (106/146) of patients repaired HR-HPV-dependent cervical lesions and cleared HR-HPV, respectively. Conclusion: In this interim analysis, repairing of HR-HPV-dependent low-degree cervical lesions and clearing HR-HPV, in real life conditions, was achieved after 6-month treatment with Papilocare® (or extending it up to 12-months if needed) in 3 out of 4 patients. These findings need to be confirmed upon study completion. Disclosures: Funding: Procare Health Disclosure: J.Cortés: Advisory/Consulting Role and Speaker at Procare Health. Y. Gaslain: CEO of Procare Health. All other authors have declared no conflicts of interest.